2016
DOI: 10.1111/ggi.12770
|View full text |Cite
|
Sign up to set email alerts
|

Multiple impacts of an intergenerational program inJapan: Evidence from theResearch onProductivity throughIntergenerationalSympathyProject

Abstract: Compelling evidence supporting the benefits of social engagement in older adults has been increasingly discussed. However, knowledge regarding an intergenerational program is limited. Herein, we provide a targeted review of intergenerational programs by focusing on our novel interventional program, Research on Productivity through Intergenerational Sympathy. The Research on Productivity through Intergenerational Sympathy program is an intergenerational picture-book reading program launched in 2004. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 32 publications
1
58
0
2
Order By: Relevance
“…The results showed a significant effect of yoga exercise and intergenerational interaction in experimental groups on general health scores and subscales of social dysfunction and depression compared to checks and pretests. These results are consistent with previous researchers ' findings that yoga exercises [13,20] and intergenerational interaction [21,22] are effective in improving health scales that are psychologically similar to anxiety, depression, and social functions. This finding is explained, yoga exercises can be said to increase physiological factors such as norepinephrine associated with alertness and dopamine associated with the pleasure mechanism, which has beneficial psychological effects of improving mood and cell activity, stress reduction, enhancement of the immune system improve attitudes towards oneself and life, increase self-esteem, energy and ultimately improve overall health [20].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed a significant effect of yoga exercise and intergenerational interaction in experimental groups on general health scores and subscales of social dysfunction and depression compared to checks and pretests. These results are consistent with previous researchers ' findings that yoga exercises [13,20] and intergenerational interaction [21,22] are effective in improving health scales that are psychologically similar to anxiety, depression, and social functions. This finding is explained, yoga exercises can be said to increase physiological factors such as norepinephrine associated with alertness and dopamine associated with the pleasure mechanism, which has beneficial psychological effects of improving mood and cell activity, stress reduction, enhancement of the immune system improve attitudes towards oneself and life, increase self-esteem, energy and ultimately improve overall health [20].…”
Section: Discussionsupporting
confidence: 93%
“…Other quantitative research has also shown a beneficial effect on the attitudes of children towards older people: the results of one study where fourth grade students were engaged in social visits, during which they interview the elders, write mini biographies based on the interviews, and draw pictures of their partner, revealed how students were more likely to perceive elders as intelligent, healthy, or valuable (Lynott & Merola, ). Another study analysed the effects of playing board games and reading picture books to children, showing not only beneficial effects on older people (such as the improvement of physical and psychological functioning), but also improving the attitudes of children towards older people (Yasunaga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these quantitative studies have their limitations: a reduction in the interaction between children and older people following a break period in the intervention – suggesting that children required more time to get back into the routine of the programme was evident (Belgrave, ); perceiving older people as a homogenous population within sampling without distinguishing any demographic or other social differences (Liu et al, ); a failure to account for why some older people were non‐responsive within the interventions (Newman & Ward, ); high dropout rates between the intervention and follow‐up (Yasunaga et al, ); and a failure to fully account for children's previous experience with older people and how this may influence their perceptions (Kamei et al, ). Most of these limitations could have been addressed by the inclusion of a qualitative element in the design to capture the lived experience of the participants involved in the study (Sasso et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in the American program "Experience Corps" senior citizens act as mentors in elementary schools (Varma et al, 2015). Other common IG activities include reading (Isaki and Harmon, 2014;Yasunaga et al, 2016), singing (Bales et al, 2000;Belgrave, 2011), playing games (Low et al, 2015), and participating to artistic projects (Teater, 2016). Despite the wide range of potential shared activities, the IG programs can be summarized in four main groups: elder people taking care of the youth, children visiting, and assisting senior citizens, elders and children cooperating in voluntary works, youth and elders who participate collectively to learning or leisure activities (Hatton-Yeo and Toshio, 2000).…”
Section: Introductionmentioning
confidence: 99%